2011
DOI: 10.1152/ajpheart.01194.2010
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrimeric Gi/Goproteins modulate endothelial TLR signaling independent of the MyD88-dependent pathway

Abstract: The innate immune recognition of bacterial lipopolysaccharide (LPS) is mediated by Toll-like receptor 4 (TLR4) and results in activation of proinflammatory signaling including NF-B and MAPK pathways. Heterotrimeric G proteins have been previously implicated in LPS signaling in macrophages and monocytes. In the present study, we show that pertussis toxin sensitive heterotrimeric G proteins (G␣i/o) are involved in the activation of MAPK and Akt downstream of TLR2, TLR3, and TLR4 in endothelial cells. G␣ i/o are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…ERK1/2 phosphorylation (10), indicating that TLR4 may transactivate a GPCR to promote signaling (25). Moreover, Dauphinee et al demonstrated that Gα i proteins modulate endothelial TLR signaling independent of TRAF6 (26). Thus, we propose a signaling model of Gα i1 and Gα i3 -mediated activation of the Gab1-PI3K-Akt-NF-κB pathway in response to LPS.…”
Section: Discussionmentioning
confidence: 91%
“…ERK1/2 phosphorylation (10), indicating that TLR4 may transactivate a GPCR to promote signaling (25). Moreover, Dauphinee et al demonstrated that Gα i proteins modulate endothelial TLR signaling independent of TRAF6 (26). Thus, we propose a signaling model of Gα i1 and Gα i3 -mediated activation of the Gab1-PI3K-Akt-NF-κB pathway in response to LPS.…”
Section: Discussionmentioning
confidence: 91%
“…31 CXCR4 is a G i -proteincoupled receptor, and heterotrimeric Gi proteins have recently been shown to induce the activation of MAPK and AKT signaling downstream of TLR2 independent of the adaptor protein MyD88. 32 In the present study, binding of anti-TLR2 ABs to TLR2 resulted in the activation of both ERK1/2 and AKT, the canonical signal transduction pathways of CXCR4. 33 This activation of signaling cascades by anti-TLR2 ABs was similar to signaling induced by direct CXCR4 activation by its ligand SDF-1, and immunoprecipitation in fact revealed an association of CXCR4 with TLR2 on binding of anti-TLR2 ABs.…”
Section: Discussionmentioning
confidence: 46%
“…[228][229][230][231][232][233][234] Treatment with the TLR2 agonist Pam3Cys has been reported to activate p38-MAPK, JNK and ERK5, but not ERK1/2 in HUVECs, and p38-MAPK, JNK and ERK1/2 in HMVECs. 31,235 Treatment with the TLR4 agonist LPS has been reported to activate p38-MAPK and JNK in HUVECs, and p38-MAPK, JNK and ERK1/2 in HMVECs. 214,235,236 Finally, treatment with the TLR9 agonist CpG DNA has been reported to activate p38-MAPK, but not ERK1/2, in mouse lung endothelial cells.…”
Section: Mapksmentioning
confidence: 99%
“…31,235 Treatment with the TLR4 agonist LPS has been reported to activate p38-MAPK and JNK in HUVECs, and p38-MAPK, JNK and ERK1/2 in HMVECs. 214,235,236 Finally, treatment with the TLR9 agonist CpG DNA has been reported to activate p38-MAPK, but not ERK1/2, in mouse lung endothelial cells. 9 Because of the importance of the conventional MAPKs in endothelial cell signaling, and because there are some apparent differences in the role of the ERKs in endothelial cells and leukocytes, each is reviewed in more detail below.…”
Section: Mapksmentioning
confidence: 99%